RASIO LEGIS DISPENSASI USIA PERKAWINAN DALAM UNDANG-UNDANG NOMOR 16 TAHUN 2019 TENTANG PERUBAHAN UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN - Farchan Anas; Fathurrahman Alfa; Humaidi Kahari (Jurnal Hikmatina, 2021)
Marriage is an inner and outer bond between a man and a woman as a happy and eternal husband and wife based on the One Godhead. This has been regulated in Law Number 16 of 2019 concerning marriage, which regulates marriage, one of which is the minimum age limit for marriage. However, this study focuses more on the ratio of the legal age of marriage dispensation according to the law. This study presents the problems and views that are studied in concepts and behavior in social life, namely qualitative research with descriptive research. Data collection techniques used are observation, interviews, and documentation. Based on this research, the results of the study show that, first, the age dispensation according to the Marriage Law is someone who wants to get married but is less than 19 years old. when the bride is not of that age, she can apply for dispensation to the religious court. Two, the comparison of this marriage law is, the difference in the minimum age limit for marriage of prospective brides from 16 years to 19 years as stated in article 7 paragraph (1) but this change has caused a lot of polemics in the community.